Magnetostrictive and Electroconductive Stress‐Sensitive Functional Spider Silk. (25th August 2022) - Spizzo, Federico; Greco, Gabriele; Del Bianco, Lucia; Coïsson, Marco; Pugno, Nicola M.
Abstract: Electronics and soft robotics demand the development of a new generation of hybrid materials featuring novel properties. Among these, remarkable mechanical properties are required to sustain mechanical stresses, and electrical and magnetic properties are essential to design the devices' interface. In this study, a hybrid material is presented, consisting of a spider silk thread, providing mechanical robustness, coated with a layer of a magnetostrictive FeCo alloy, which ensures both electrical conductivity and stress‐sensitive magnetic properties. The durability and the homogeneity of the composite are validated, as well as its ability to respond to magnetic and mechanical stimuli. Despite the coating, the soft nature of the silk and its mechanical performances are preserved. The magnetic study reveals that the magnetic behavior of the film is strongly affected by the silk thread–FeCo layer interaction, especially under mechanical stresses. Indeed, when the composite is subjected to tensile strain, the magnetic signal changes accordingly, indicating that the layer–silk interaction is maintained and can be exploited to reveal the tensional state of the sample even under severe cycles. Therefore, the presented hybrid material is a flexible fiber with properties that are suitable for magneto‐electronics applications, e.g., magnetic actuators as well as strain/stress sensors. Abstract : Mechanically robust spider silk threads are coated with a magnetostrictive FeCo alloy that provides electrical conductivity and stress‐sensitive magnetic properties. The hybrid system here designed is soft, durable, and promptly responds to magnetic and mechanical stimuli. The complete mechanical, electric, and magnetic characterization shows that this spider silk based component can be used for soft electronics and robotics applications.